The Halodoc’s Social Media Data Analysis Amidst Covid-19 Pandemic: An Evidence from Indonesia - Hilarius Bambang Winarko; Diana Intan Pratiwi; Linda MacGrain Herkenhoff (Institut Teknologi Sepuluh Nopember, 2023)
This study aims to analyze Halodoc telehealth services reputation through its social media during Covid-19 pandemic critical time of 2020-2021 by using big data analysis. During that period, more people increasingly used e-health application services. This study applies data scraping technique to analyze big data collected from Halodoc’s social media official accounts. The analysis includes contents, views, comments, likes, dislikes, and shares from the audiences toward Halodoc’s social media platforms. The results indicate that Halodoc’s brand reputation is considered positive. YouTube was the Halodoc’s social media platform that most got attention from customers’ actions (views, likes, comments, and dislikes). Meanwhile, its Instagram was the most demanded by customers because they wanted to win the prizes from Halodoc. And finally, Facebook was the less communicative social media platform, due to the problem on handling the Covid-19 tests. Several issues need to be resolved by Halodoc to further meet the user experience’s expectations.